Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI): Strategi Meningkatkan Hasil Belajar Matematika Siswa di Sekolah Dasar - Harpan Reski Mulia; Derliani Daulay (MAN 4 Kota Pekanbaru, 2026)
This study investigates the application of the indonesian realistic mathematics approach (PMRI) in teaching integers and its impact on students’ learning outcomes. Employing two-cycle classroom action research (CAR) design, the study involved 18 sixth-grade students at MIN 11 Aceh Tenggara in the 2024/2025 school year. Data were collected through structured observation and objective tests and analyzed using Pearson’s product moment correlation. The results showed improvement in both implementation and outcomes: the first cycle reached an average score of 79.31 (good) and the second cycle 92.24 (very good). Student mastery also increased, with 61% exceeding the minimum mastery criteria (KKM) in cycle I and 83% in cycle II. The correlation analysis produced a coefficient of 0.592, indicating a moderate positive relationship between the two cycles.